Formation of Innovative Activities of Technology Teacher - Shodmonova Zilola Bozorovna (Journal of Higher Education and Academic Advancement, 2024)
This article analyzes the motives of amateur performance, creativity and creativity in the activities of a technology teacher, and in order to create a new situation of communication, the teacher should influence the creativity of his personality, introduce innovations, a new situation of communication is a new situation of communication. This is explained by the teacher's ability to create his own position of independence, pedagogical science, a new attitude towards himself.